Overexpression of WDR79 in non‐small cell lung cancer is linked to tumour progression. Issue 4 (5th February 2016) - Sun, Yang; Yang, Chao; Chen, Jieying; Song, Xin; Li, Zhen; Duan, Minlan; Li, Jianglin; Hu, Xiaoxiao; Wu, Kuangpei; Yan, Guobei; Yang, Cai; Liu, Jing; et al.
Abstract: WD‐repeat protein 79 (WDR79), a member of the WD‐repeat protein family, acts as a scaffold protein, participating in telomerase assembly, Cajal body formation and DNA double‐strand break repair. Here, we first report that WDR79 is frequently overexpressed in cell lines and tissues derived from non‐small cell lung cancer (NSCLC). Knockdown of WDR79 significantly inhibited the proliferation of NSCLC cells in vitro and in vivo by inducing cell cycle arrest and apoptosis. WD‐repeat protein 79 ‐induced cell cycle arrest at the G0/G1 phase was associated with the expression of G0/G1‐related cyclins and cyclin‐dependent kinase complexes. We also provide evidence that WDR79 knockdown induces apoptosis via a mitochondrial pathway. Collectively, these results suggest that WDR79 is involved in the tumorigenesis of NSCLC and is a potential novel diagnostic marker and therapeutic target for NSCLC.